(untitled) ("Temas Sociais" Journal, 2023)
Human beings have always been facing various obstacles over several generations, but in the past four years they have come face to face with the COVID-19 pandemic and its lockdowns, the possibility of 3rd World War, climate change, natural disasters, rising inflation and many other difficulties. This study aims to assess the perception of emotional intelligence, resilience and occupational stress in social workers working in mainland Portugal and the islands, focusing on a sample of 237 individuals, 215 female and 22 male, aged between 21 and 73. The Wong and Law Emotional Intelligence Scale, the Brief Resilience Coping Scale and the Oldenburg Burnout Inventory were applied. The results showed that the sample had a high average perception of emotional intelligence and an average ability to regulate their own emotions. In terms of resilience, the sample revealed average results. Occupational stress is evident, resulting in medium/low values for the ability to detach and the perception of exhaustion. It was concluded that the participants have an average perception of emotional intelligence and resilience to respond adaptively to the effects of stress arising from the context in which they find themselves.